2018
DOI: 10.17533/udea.rfnsp.v36n1a08
|View full text |Cite
|
Sign up to set email alerts
|

Exposición a Bisfenol A (BPA) en mujeres embarazadas y su relación con la obesidad en sus hijos: revisión sistemática

Abstract: Pregnant women's exposure to Bisphenol A (BPA) and its relation to their children's obesity: systematic review Exposição ao bisfenol a (BPA) em mulheres engravidadas e a sua relação com a obesidade em seus filhos: revisão sistemática

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(78 reference statements)
0
2
0
2
Order By: Relevance
“…El producto tóxico del cigarrillo actúa sobre el lecho vascular y provoca alteraciones circulatorias, lo que atenta contra la oxigenación, la nutrición fetal y, por ende, ocasiona bajo peso al nacer (23). De la misma manera, la presencia de disruptores endocrinos, como el bisfenol A, comúnmente encontrado en cigarrillos, puede conllevar alteraciones hormonales que afectan las medidas antropométricas del bebé (24).…”
Section: Discussionunclassified
“…El producto tóxico del cigarrillo actúa sobre el lecho vascular y provoca alteraciones circulatorias, lo que atenta contra la oxigenación, la nutrición fetal y, por ende, ocasiona bajo peso al nacer (23). De la misma manera, la presencia de disruptores endocrinos, como el bisfenol A, comúnmente encontrado en cigarrillos, puede conllevar alteraciones hormonales que afectan las medidas antropométricas del bebé (24).…”
Section: Discussionunclassified
“…A number of systematic and literature reviews were identified, focusing on a small number of classes of plastic chemicals (e.g. phthalates) and bisphenol A [ 52 55 ] and certain associated diseases [ 56 , 57 ]. These systematic and literature reviews addressed only a few specific chemicals and did not evaluate non-disease-specific health domains, such as changes in gene expression, oxidative stress and the microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary searches conducted in Prospero, Epistimonikos, Cochrane, Medline (Ovid) and Embase (Ovid) databases in May 2020 did not identify any previous or current scoping review on this broad topic. A number of systematic and literature reviews were identified, focusing on a small number of classes of plastic chemicals, such as phthalates, and bisphenol A (5255), and certain diseases associated with these chemical species (56,57). These systematic and literature reviews addressed only a few specific chemicals and did not evaluate non disease-specific health domains, such as changes in gene expression, oxidative stress and the microbiome.…”
Section: Introductionmentioning
confidence: 99%